139k views
2 votes
F(x) = x + 5 and g(x) = 2x Find (f +g)(x)

User Walther
by
5.9k points

1 Answer

7 votes

Answer:

Step-by-step explanation:f

(

x

)

=

2

x

g

(

x

)

=

x

+

5

Set up the composite result function.

f

(

g

(

x

)

)

Evaluate

f

(

g

(

x

)

)

by substituting in the value of

g

into

f

.

f

(

x

+

5

)

=

2

(

x

+

5

)

Apply the distributive property.

f

(

x

+

5

)

=

2

x

+

2

5

Multiply

2

by

5

.

f

(

x

+

5

)

=

2

x

+

10

User Loadaverage
by
6.0k points